The Effects of Prepaid Metering Systems on Customer Satisfaction in Niger State, Nigeria - Ayooluwa Femi Aribisala; Musa Mohammed (Journal of Digital Food, Energy & Water Systems)
Energy consumers in Nigeria have long complained about Distribution Companies' unfair billing practices, exorbitant monthly electricity bills resulting from meter estimation rather than accurate meter reading and calculation based on uninterrupted electricity use. The objectives of the study were to establish the relationship between the prepaid metering system and customer satisfaction; and to evaluate the level of satisfaction with respect to the usage of the prepaid metering system in Niger State, Nigeria. In carrying out the study, the structured questionnaire was administered to 393 randomly chosen respondents drawn from prepaid meter users, out of which 344 responded generating a response rate of 87.5%. The data derived were subjected to spearman correlation and multiple regression models. The major findings from the study showed a significant, moderate and positive relationship between the prepaid metering system and customer satisfaction. Additionally, three significant predictors, Affordability, Availability and Flexibility with p < .01 are statistically significant. Further findings from descriptive statistics revealed that users had the highest level of satisfaction with the privacy they had as a result of no meter readers and no accumulated. The study concluded that there exist a positive and beneficial link between the prepaid metering system and customer satisfaction. The study therefore recommends the provision of a smart metering system, good customer care units and a marketing campaign for better knowledge of the prepaid metering system.